Quality Optimization of Fuel Transportation Tank Production Process Using Design of Experiment (DoE) at PT. Sejahtera Mandiri Pekanbaru - Putra, Ahmad Mahatanzie; Anizar; Panjaitan, Nismah (TALENTA Publisher, 2025)
With an average error rate of 2.3%, the production of fuel transportation tanks at PT Sejahtera Mandiri Pekanbaru has defects that exceed the 2% tolerance level. Porosity, undercut, and crack are the most frequent types of defects that result in additional cost and rework time. This study aims to improve the quality of the fuel transportation tank production process at PT Sejahtera Mandiri Pekanbaru. Data shows that production errors such as porosity, undercut, and cracks have an impact on the quality of the final product. This study used a 2k full factorial design to find the main components that affect the quality of welding results. The results show that operator certification and electrode temperature oven parameters have a great influence on manufacturing defects. Maximizing the use of electrode oven at 260°C-425°C for 1 hour, electrode moisture can be eliminated and porosity can be reduced. The DoE approach is good for finding and optimizing production features to reduce defect rates. This study suggests operator training and control of process parameters to improve welding quality.